Islamic Work Ethics in Thwarting Knowledge-Hiding Behavior among Organization Members - Muhammad Rasyid Abdillah; Rizqa Anita; Adi Rahmat; Zulhendra Zulhendra; Fahmi Oemar (IQTISHADIA, 2023)
Knowledge-hiding (KH) behavior is of particular concern in organizational and management studies because it can reduce the flow of knowledge and information in organizations. Thus, mechanisms that can minimize this behavior need to be identified, especially from an Islamic perspective. This study seeks to explain how Islamic work ethics may decrease or thwart employees from performing KH. In particular, the current study tries to explain the dual mediation mechanism that underlies this relationship, namely organizational citizenship behavior (OCB) and organizational commitment (OC). In order to verify the hypotheses, this study collected data from employees who work at Islamic banks in Pekanbaru City, Riau, Indonesia. Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis was employed to verify the hypotheses proposed in the current study. This study revealed that Islamic work ethics can potentially limit or thwart workers from successfully performing their KH. Furthermore, this study found that organizational commitment and OCB mediate the mechanisms underlying the relationship.